Produksi Program Acara Pro 2 Activity di Pro 2 RRI Semarang (Produser) - Dicky Aditya Wijaya; adi Nugroho (Interaksi Online, 2020)
Radio is one of the mass media which has been around for a long time and has survived until the era of new media convergence. Radio midst of easy access to various new media to obtain information and entertainment. Radio Republik Indonesia (RRI) is the first radio station owned by the Government of Indonesia and was officially established on September 11, 1945. Radio Republik Indonesia (RRI) has 35 regional stations spread across various parts of the archipelago. RRI Semarang is one of the oldest radio stations in the city of Semarang. This radio has four channels and has a special channels aimed at youth segmentation. The channel is Pro 2 RRI. Pro 2 RRI has several programs, one of which is "Pro 2 Activity". "Pro 2 Activity" program is a daily program that is broadcast every day at 06:00 to 09:00 o’clock with a duration of 180 minutes. This radio talk show infotainment program genre, discusses various information that is becoming a trend and actual, especially among young people, accompanied by a talk show on the third hour by presenting speakers from among young people. But in the process, this program has a small number of listener responses. This is the reason why the writer and the other Field Works production team to produce this program with a new concept for 24 episodes. This program will add several innovations in the form of broadcast packages such as earcatcher, paparazy (radio play), viral interlude (selvi), and vox pop to attract more enthusiastic listeners. In the production of the program "Pro 2 Activity" for 24 episodes or within a period of 2 months the author served as a Producer. The author is overall responsible during the program production process, both in pre-production, production and post-production. After the "Pro 2 Activity" program was packed with new concepts for 24 episodes, there was a significant increase in the number of listeners. The average number of listeners of the "Pro 2 Activity" program per previous episode is 4-5 people. However, after the production team repackaged the program with a new concept, the average number of listeners per episode increased to 8-10 people.